The automatization of press statistics as one of the ways to improve the service of information users - Angelė Šarlauskienė (Knygotyra, 1990)
The Department of Press Statistics at the Book Palace of Lithuania is the first in the Soviet Union to apply computers for preparing quick accounts of gathered information. This significantly helps to regulate book production and its thematic planning. The Department of Press Statistics functions independently as a constituent part of the automatization of press statistics in the Book Palace.